Perlindungan Hukum Waralaba Di Indonesia - Sumiyati, Sumiyati; Rani, Rani Apriani (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Competition in the business world is getting tougher and tighter. This encourages entrepreneurs, both large and small scale, to compete to face business competition and strive for their business to continue to exist. One of the ways that entrepreneurs do in expanding their business is to open a franchise business system or franchise. The essence of franchising is a contract agreement regarding the distribution system of goods and services to consumers. In the agreement between the giver and the franchisee, there are rights and obligations that must be fulfilled by both parties. Therefore, regulatory protection is needed for both parties so that both parties benefit from each other and do not feel disadvantaged. This study uses normative legal methods by presenting secondary data. In this study, franchisors and franchisees will receive legal protection after carrying out the procedures regulated in Government Regulation Number 42 of 2007, namely registering franchise agreements and recording franchise agreements.